O lugar da mulher negra na cidade: da marginalização ao encarceramento - Costa, Micaela Rodrigues da (Universidade Federal de São Carlos, 2024)
The mass incarceration of women is a pressing concern of our time, disproportionately affecting Black women. This study aims to analyze and contextualize the living conditions of Black women in the city. To achieve this, we interviewed two Black women and one white woman from the eastern zone of São Paulo, shedding light on the debate surrounding Brazil's structural racism, of which incarceration is one manifestation. Through a materialist and dialectical historical analysis, we seek to understand the dynamics that permeate female incarceration while also sharing the life stories of these women.
The place of black women in the city: from marginalization to incarceration
Keywords: Encarceramento em Massa; Mulheres Negras; Sistema Prisional; Mass Incarceration; Black Women; Prison System; CIENCIAS HUMANAS